An exploratory study on the impact of the yeast strain on hop flavour expressions in heavily hopped beers: New England IPA - Van Opstaele, Filip; De Rouck, Gert; Janssens, Philippe; Montandon, Gabriela Gontijo (BrewingScience, 2020)
YEAST SPECIAL In this study, the role different yeast strains might play in the flavour characteristics of heavily hopped beers was investigated. Therefore, New England Indian Pale Ale (NEIPA) style beers were brewed according to a standard brewing procedure in which all brewing parameters were kept constant with the exception of the yeast strain used for fermentation. In total, nine NEIPA beers were produced with nine different beer yeasts (seven ale yeasts (Saccharomyces cerevisiae) amongst which five strains are phenolic off flavour negative (POF-) and two strains are POF positive); two lager yeasts (Saccharomyces pastorianus, POF-). Via descriptive sensory evaluations, the beers were distinguished into several clusters which demonstrated the impact of the yeast strain on the final flavour attributes of the resulting beers. Particular yeasts strains boosted juicy and fruity flavours whereas others significantly suppressed the hop-derived aroma of the NEIPA beers in this comparative study. Analytical results point into the direction of yeast strain induced variability in the levels of (flavour-active) hop oil constituents and/or synergistic effects between yeast aromas and hop aromas as possible explanations for the flavour differences of the final beers.